Stress rupture properties and deformation mechanisms of K4750 alloy at the range of 650 °C to 800 °C. Issue 7 (July 2019) - Ou, Meiqiong; Ma, Yingche; Xing, Weiwei; Hao, Xianchao; Chen, Bo; Ding, Leilei; Liu, Kui
Abstract: The stress rupture properties and deformation mechanisms of K4750 alloy at 650 °C, 700 °C, 750 °C and 800 °C were investigated. As the decrease of temperature and stress, the stress rupture life gradually increased. A Larson-Miller Parameter (LMP) method was used for analyzing the stress rupture life under different conditions. The linear fitting formula between stress ( σ ) and LMP was derived as σ = 3166.455 − 119.969 × LMP and the fitting coefficient was 0.98. After testing, the dislocation configurations of all stress rupture samples were investigated by transmission electron microscopy (TEM). The temperature and stress had a significant impact on the deformation mechanism, thereby affected the stress rupture life of K4750 alloy. As the increasing stress at a given temperature, the deformation mechanism gradually transformed from Orowan looping to stacking fault shearing. Based on experimental results, the threshold stress at 650 °C, 700 °C, 750 °C and 800 °C for the transition of deformation mechanism was estimated to be about 650 MPa, 530 MPa, 430 MPa and 350 MPa, respectively. Below the threshold stress, γ ' phase effectively hindered dislocation motion by Orowan looping mechanism, K4750 alloy had a long stress rupture life. Slightly above the threshold stress, Orowan looping combining stacking fault shearing was the dominant mechanism, the stress rupture life decreased. As the further increase of stress, stacking fault shearing acted as the dominant deformation mechanism, the resistance to dislocation motion decreased rapidly, so the stress rupture life reduced significantly.